Clinical care ratios for, and tasks undertaken by, allied health professionals: A scoping review of the literature. - Arabella Brown; Elias El-Achkar; Francesca Fragnito; Sandra Gosnell; Jocelyn Kelly; Daniel Kucharski; Alice Priestly; Saravana Kumar (PLoS ONE)
Background With the increasing demand on the global health system and the presence of persistent healthcare disparities, it becomes imperative to utilize the full potential of the healthcare workforce, including allied health professionals (AHPs). To date, no review has mapped the literature on clinical care ratios (CCRs) for AHPs. This information is vital in guiding future work-force planning to address healthcare issues such as understaffed and at capacity hospitals. This scoping review mapped available evidence to offer a comprehensive insight into current AHP CCRs, enabling evidence-based decision-making that ensures optimal care and enhanced system efficiency. Methods The scoping review was undertaken using the 'Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews' (PRISMA-ScR). The search was conducted using Ovid (MEDLINE, Embase, Emcare, PsycINFO), CINAHL, the Cochrane Library, Scopus, PEDro, OTseeker and grey literature. Two reviewers independently screened records, following which data extraction was completed for the included studies. Descriptive synthesis was used to summarize the data. Results Of the 7670 records identified, 18 studies were included in this review. Whilst there was variability between AHPs on direct clinical time spent with patients, considerable amount of time was also spent on activities beyond direct clinical care. To offset this, literature highlights opportunities for allied health assistants and students to undertake tasks which would free-up AHPs to undertake more direct and higher-level tasks. However, limitations of findings (variability in measurement, lack of coverage of some professions) limits generalisability. Conclusion While the literature highlights considerable variability in CCRs among different AHP disciplines, it does appear nearly a nearly a third of time spent by AHPs are on tasks that are beyond direct clinical care. Future research could explore new workforce models which would free-up AHPs to undertake more direct and higher-level tasks.